2022
DOI: 10.1021/acsami.2c15881
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate-Derived Paclitaxel Nanocrystal via π–π Stacking with Enhanced Stability and Tumor Targetability

Abstract: Nanocrystals with high drug loading have become a viable strategy for solubilizing drugs with poor aqueous solubility. It remains challenging, however, to synthesize nanocrystals with sufficient stability and targeting potential. Here, we report a novel nanocrystal platform synthesized using paclitaxel (PTX) and Fmoc-8-amino-3,6-dioxaoctanoic acid (Fmoc-AEEA)conjugated chondroitin sulfate (CS) (CS-Fmoc) via π−π stacking to afford a stable formulation with CD44 targetability (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Regarding the 1 H NMR spectrum of CS-NH 2 (Figure S2b), structural modifications were validated at peaks of 1.95 (a, 3H, CH 3 –CONH 2 ), and 2.34 ppm (b, 4H, NH 2 (CH 2 ) 2 NHCO). As for CS-Fmoc (Figure S3b), the appearance of the signature peak at 7.33–7.99 ppm demonstrated that Fmoc-AEEA was successfully introduced into CS-NH 2 . Meanwhile, the substitution degree of Fmoc-modified CS was about 26.6%.…”
Section: Results and Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Regarding the 1 H NMR spectrum of CS-NH 2 (Figure S2b), structural modifications were validated at peaks of 1.95 (a, 3H, CH 3 –CONH 2 ), and 2.34 ppm (b, 4H, NH 2 (CH 2 ) 2 NHCO). As for CS-Fmoc (Figure S3b), the appearance of the signature peak at 7.33–7.99 ppm demonstrated that Fmoc-AEEA was successfully introduced into CS-NH 2 . Meanwhile, the substitution degree of Fmoc-modified CS was about 26.6%.…”
Section: Results and Discussionmentioning
confidence: 84%
“…CS-Fmoc was synthesized via a two-step amide reaction as previously described . Briefly, 10 mL of 51.5 mg/mL CS solution was mixed with 1.342 g of EDC and 0.845 g of NHS to activate the carboxyl group, which then dripped it into the 5.58 mL ethylenediamine solution on an ice bath and stirred at room temperature for 3.5 h, then dialyzed, and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations